Rapid Intraocular Tube Trimming for Glaucoma Drainage Implant Devices. Issue 5 (May 2017) - Baciu, Paul; Moster, Stephen J.; Lee, Richard K.
Abstract : Purpose: To describe a new approach for shortening silicone tubes of glaucoma drainage devices (GDDs). Materials and Methods: A retrospective intervention case series describing 3 patients undergoing the same treatment at a single institutional center Results: Three patients underwent successful ab interno trimming of GDD silicone tubes without complication Conclusions: This technique allows for rapid and successful shortening of GDD tubes via an ab interno approach avoiding risks of traditional glaucoma tube trimming approaches. Abstract : Supplemental Digital Content is available in the text.